Does individualistic culture impact operational risk?. (11th November 2019) - An, Zhe; Cao, Zhe; Chen, Zhian; Li, Donghui
Abstract: Employing a sample of 2, 957 operational‐risk events across 31 countries from 1990 to 2011, we find that financial institutions located in countries with higher individualism tend to have higher operational risk. This positive relation is achieved through the risk‐taking channel and the earnings‐management channel. In addition, the magnitude of operational losses is higher in more individualistic countries. The results suggest that individualism serves as an important informal institutional determinant of operational risk in an international context. Endogeneity tests and various robustness checks confirm our findings.